Karakteristik Kepribadian Ditinjau Dari Preferensi Musik Pada Mahasiswa Di Banda Aceh - Sarbulis Sarbulis; Afriani Afriani; Marty Mawarpury; Syarifah Faradina (Syiah Kuala Psychology Journal, 2023)
Musik adalah salah satu bentuk seni yang sangat dekat dengan keseharian manusia. Preferensi musik yang dimiliki seseorang dapat digunakan untuk mengungkapkan karakteristik-karakteristik dari kepribadiannya. Penelitian ini bertujuan untuk mengetahui bagaimana hubungan antara preferensi musik dengan kepribadian pada mahasiswa di kota Banda Aceh. Sampel penelitian ini adalah 352 mahasiswa (18-25 tahun) di kota Banda Aceh yang dipilih menggunakan teknik cluster dan proportionate stratified random sampling. Pengumpulan data dilakukan dengan menggunakan skala Short Test of Music Preference (STOMP) untuk mengukur preferensi musik dan skala Ten Item Personality Inventory (TIPI) untuk mengukur kepribadian. Hasil analisis menunjukkan terdapat hubungan antara preferensi musik upbeat and conventional (r=0,10, p0,05), energetic and rhythmic (r=0,11, p0,05), intense and rebellious (r=0,16, p0,01) dengan trait kepribadian extraversion; preferensi musik upbeat and conventional dengan trait kepribadian agreeableness (r=0,14, p0,01); preferensi musik upbeat and conventional (r=0,15, p0,01) dengan trait kepribadian conscientiousness; preferensi musik reflective and complex (r=0,12, p0,05), upbeat and conventional (r=0,14, p0,01), intense and rebellious (r=0,11, p0,05) dengan trait kepribadian emotional stability; preferensi musik reflective and complex (r=0,11, p0,05), upbeat and conventional (r=0,11, p0,05), intense and rebellious (r=0,12, p0,05) dengan trait kepribadian openess to experience. Berdasarkan hasil penelitian ini, dapat disimpulkan bahwa preferensi musik berkaitan dengan karakteristik kepribadian seseorang.Music is one of art that very near to everyday human life. A person's music preference can be used to reveal the characteristics of his personality. The aimed of this study was to determine the relationship between music preferences with personality among students in Banda Aceh. The sample were 352 students (18-25 years old) in Banda Aceh that selected using cluster technique and proportionate stratified random sampling. The data were measured using Short Test of Music Preference (STOMP) to measure the music preferences and Ten Item Personality Inventory (TIPI) to measure the personality. The results of analysis found that there were significant relationships between upbeat and conventional (r=0,10, p0,05), energetic and rhythmic (r=0,11, p0,05) intense and rebellious (r=0,16, p0,05) music preferences with extraversion personality trait; upbeat and conventional music preference (r=0,14, p0,05) with agreeableness personality trait; upbeat and conventional music preference (r=0,15, p0,05) with conscientiousness personality trait; reflective and complex (r=0,12, p0,05), upbeat and conventional (r=0,14, p0,05), intense and rebellious (r=0,11, p0,05) music preferences with emotional stability personality trait; reflective and complex (r=0,11, p0,05), upbeat and conventional (r=0,11, p0,05), intense and rebellious (r=0,12, p0,05) music preferences with openess to experience personality trait. In conclusion, the study showed that music preferences are related to ones personality.